BAGAIMANA GAYA KEPEMIMPINAN MEMOTIVASI PARTISIPASI DALAM BADAN USAHA MILIK DESA? - Theotama, Gracella; Puspitasari, Mika; Yefta Andi Kus Nugroho (E-Jurnal Akuntansi TSM, 2025)
Villagers participation in the growth of the economic village plays an important role. Forms of villager participation can be implemented through Village Owned Enterprises (BUMDes). BUMDes must be able to create a good ecosystem so that it can be trusted by the villagers. Therefore, leaders are needed who can energize the ecosystem optimally. So, this research aims to discuss the influence of leadership style in increasing villagers participation in BUMDes KITA, Central Wologai Village, Ende Regency, East Nusa Tenggara. This research uses primary data obtained by interviews through Forum Group Discussion (FGD). The research shows that a transformational leadership style increases the trust of villagers. So, the villagers participation in managing BUMDes is more optimal. Practically, this research can be used as a reference for other BUMDes management.